FUNGSI KOGNITIF MEMILIKI HUBUNGAN DENGAN KEMANDIRIAN ACTIVITY DAILY LIVING LANSIA - Suspiyanti, Dian; Huriah, Titih; Lestari, Ratna (Universitas Jenderal Achmad Yani Yogyakarta, 2014)
Background: The increasing number of the elderly will become problems due to the aging process. The aging process in elderly has many aspects of life especially in health problem, one of them is the cognitive function. The cognitive problem will be a serious problem because it attacks the elderly?s thought. The cognitive destruction on the elderly known as demensia. Sliding scale of demensia will influence the social activities, normal occupation and daily activities whereas the daily activities are important to the viability, health and prosperity of the elderly. Objective: The study aimed to know between cognitive function with the independency of the elderly in fullfiling activity daily living in Jodog Village, Gilangharjo District, Pandak, Bantul. Methods: The study used a cross sectional design. The data collection used proportional random sampling methode, with the number of 62 elderly. The data are collected using MMSE and Katz Index questionaire. The data analysis method used the univariat and bivariat analysis of Kendall?s tau with p<0,05. Results: The result of cognitive function showed that 11,3% of the elderly have average level of cognitive function, 56,5% have light interruption level of cognitive function, and 3,2 % have heavy destruction level of cognitive function. The assesment of independency of the elderly in doing activity daily living shows that the indepency of the elderly in category A (35,5%), B (19,4%), C (17,7%), D (14,5%), E (4,8%), F (1,6%) and G (6,5%). The result of Kendall?s tau correlation between cognitive function with the indepency of the elderly in doing daily activities has 0,003 significance level (0<0,05) with the lowest correlation strength (coefficient correlation 0,321). Conclusion: There was a correlation between cognitive function and independency elderly in the doing activity daily living. Suggestion : The result of study can give more information for cadre at Jodog Village about the value of elderly cognitive impairment and independency of activity daily living. Keywords: Elderly?s cognitive ability, independency in activity daily living.